An enhanced inventory of global dams and reservoirs and their contribution to sea level - Walter, Blake Allen (Kansas State University, 2018)
In the 1950s-60s, the world was experiencing a dramatic increase in artificial water impoundments in an unprecedented effort to eliminate spatial and temporal variations in water accessibility. Dam construction has since decreased, but recently, efforts to supply water and power to a booming world population may once again spark another dam construction boom. Water supplies in some regions are already highly stressed in an effort to satisfy the ever-growing water demand for agriculture, industrial, and domestic uses. With nearly 30% of the world’s population living in water-scarce regions, an improved understanding of total stored surface water has never been more needed. Yet, a complete and spatially-explicit, worldwide inventory of such storage capabilities is lacking. Using several open-source dam registries and high-resolution global lake mapping datasets extracted from thousands of Landsat images, we here aim to provide an updated and spatially-explicit inventory of dams and artificial reservoirs across the world. The following research uses novel techniques to merge 5 authoritative, open-source dam registries into a single dam and reservoir dataset, which we deemed as the Global Dam and Reservoir Inventory (GDRI). In total, GDRI documents 89,500 dams and 83,767 reservoirs for a total capacity of 8,492km³ and total surface area of 754,551km². Reservoirs account for approximately 2.5% of the Earth’s terrestrial water. In other words, 1 unit of water for every 40 units has been artificially created. Further downscaling of the non-geocoded records provided by the International Commission of Large Dams (ICOLD) using similar geocoding methods allowed for the thorough use of all available ICOLD records. Additional capacity estimates from downscaled ICOLD records increased the GDRI capacity documentation to 8,603km3 and surface area documentation to 859,271km². Compared to its counterpart, the Global Reservoir and Dam dataset (GRanD), GDRI increased the number of dams documented by 1204%, reservoirs by 1127%, total capacity by 37%, and total surface area by 68%. Initial water impoundment from dam construction activities can lower sea level by permanently trapping water storage on land. Dam construction resulted in an equivalent sea level drop (SLD) of 23.4mm or 0.08mm/yr. Since the dam construction boom of the 1950s-1960s, yearly SLD increased to 0.27mm/yr. By considering the hydrological characteristics of dam location, in terms of endorheic and exorheic basins, we found that exclusion of endorheic located dams decreases the overall effect on SLD by 5.47% or 1.28mm. Failure to consider the hydrologic characteristic of dam location can result in the overestimation of dam-induced SLD. After the dam construction boom of the 1950s-1960s, the world has seen a decreasing trend in dam construction, but developing countries (China, Brazil, India) are still actively pursuing dam projects that are larger and more ambitious than ever before. We see less developed countries often lack the capabilities for dam construction possibly increasing stress on natural water supplies in those regions. The datasets produced are by no means perfect. Overall, the described procedures should be considered a heuristic model, where fastidious quality assurance and automated procedures work to thoroughly eliminate many of the issues encountered with the dataset production, but errors may still exist. However, duplication between the contributing dam datasets, spatial limitations of the lake datasets, imperfect geocoding procedures, and inclusion of more dam datasets provide opportunity for future refinement and improvement of the datasets. This research contributes vital information about anthropogenic water resources that incrementally enhances our knowledge of global hydrology and the interactions taking place between different water entities.
Keywords: Dams; Reservoirs; Sea level; Global hydrology; Inventory